Knowledge, Attitudes and Practices of Pregnant Women towards Vaccination with Tetanus-Diphtheria (Td) Vaccines and Influenza - Ali Reza Soleimani; Mohammad Sharif Khoeiniha; Mitra Rahimzadeh; Mohammad Hossein Dehghan (Tehran University of Medical Sciences, 2022)
Background and Aim: Proper knowledge, attitude and practice of pregnant women about vaccination during this period will have a significant impact on their and their baby's health. The aim of this study was to determine the knowledge, attitude and practice of pregnant women toward flu and Td vaccination. Materials and Methods: This study was a descriptive-analytical and cross-sectional study on 312 pregnant women referred to Imam Ali Hospital in Karaj with an age range of 15 to 40 years. Data were collected using a questionnaire. The method of sampling was convenience sampling. The data was analyzed using SPSS software. Results: The mean age of the women was 27.6±6.54 years. 198 (63.5%) of the subjects were housewives and 114 (36.5%) were employed. 248 (79.5%) and 282 (90.4%) of the subjects had appropriate attitudes and knowledge about vaccination with Td vaccines and Influenza, respectively. Also 293 (93.9%) and 137 (43.9%) of the subjects had practice well against both Td and Influenza vaccines. In women with higher education and better economic conditions, and in working women, the practice of both vaccines has become more suitable. As women get older, knowledge and practice about Td vaccination decreased. Also, the most common source of information for pregnant women about the vaccination program were 73.4% of health care workers, 12.5% ​​of the Internet, 10.3% of radio and television, 3.5% of friends and acquaintances, and 0.3% of family members, respectively. In the relationship between knowledge, attitude and practice towards Influenza and Td vaccination, there was a direct and significant relationship between them so that with increasing or decreasing one, the other also increased or decreased. Most of the relationship between awareness and practice items was related to Influenza vaccine (r=0.304) and the lowest relationship between knowledge with practice items was related to Td vaccine (r=0.146). Conclusion: In this study, it was found that with increasing awareness and attitude, vaccination has increased. Regarding Influenza vaccination, due to the significant relationship between the source of information and vaccination, it is recommended that more serious recommendations to be made by the health care staff to pregnant women regarding Influenza vaccination.